Dirty Secrets : How Tax Havens Destroy the Economy - Murphy, Richard (New York Verso, 2017)
"What happens when the rich are allowed to hide their money in tax havens, and what we should do about it The Panama Papers were a reminder of how the superrich are allowed to hide their wealth from the rest of us. Dirty Secrets uncovers the extent of the corruption behind this crisis and shows what needs to be done in the face of this unregulated spread of rampant greed. Tax havens, we are often told, are part of the global architecture of capitalism, providing a freedom from regulation necessary to make markets work. In this book, leading authority Richard Murphy uncovers the truth behind this lie. The fact of the matter is that this increasingly popular practice threatens the foundations of democracy, sowing mistrust and creating a regime based upon opacity. As Murphy shows, how we manage our economy is a political decision, and one that can be changed. Dirty Secrets proposes ways to regulate tax havens and what the world might look like without them"
Include Index
Keywords: Tax Haven -- Tax Evasion -- Business and Economics Taxation General